Formation and Control of the Viable but Non-culturable State of Foodborne Pathogen Escherichia coli O157:H7 - Li, Yanmei; Huang, Teng-Yi; Ye, Congxiu; Chen, Ling; Liang, Yi; Wang, Kan; Liu, Junyan (Frontiers in Microbiology, 2020)
As a common food-borne pathogen, E. coli O157:H7 produces toxins causing serious diseases. However, traditional methods failed in detecting E. coli O157:H7 cells in VBNC state, which poses a threat to food safety. This study aimed at investigating the formation, control and detection the VBNC state of E. coli O157:H7. Three factors including medium, salt, and acid concentrations were selected as a single variation. Orthogonal experiments were designed with three factors and four levels, and 16 experimental schemes were used. The formation of VBNC state was examined by agar plate counting and LIVE/DEAD® BacLightTM bacterial viability kit with fluorescence microscopy. According to the effects of environmental conditions on the formation of VBNC state of E. coli O157:H7, the inhibition on VBNC state formation were investigated. In addition, E. coli in VBNC state in food samples (crystal cake) was detected by Propidium Monoazide-Polymerase Chain Reaction (PMA-PCR) assays. Acetic acid concentration showed the most impact on VBNC formation of E. coli O157:H7, followed by medium and salt concentration. The addition of 1.0% acetic acid could directly kill E. coli O157:H7 and eliminate its VBNC formation. In crystal cake, 25%, 50%, or 100% medium with 1.0% acetic acid could inhibit VBNC state formation and kill E. coli O157:H7 within 3 days. The VBNC cell number was reduced by adding 1.0% acetic acid. PMA-PCR assay could be used to detect E. coli VBNC cells in crystal cake with detection limit at 104 CFU/mL. The understanding on the inducing and inhibitory conditions for the VBNC state of E. coli O157:H7 in typical food system, as well as the development of an efficient VBNC cell detection method might aid in the control of VBNC E. coli O157:H7 cells in food industry.